Adipocyte p53 coordinates the response to intermittent fasting by regulating adipose tissue immune cell landscape - Reinisch, Isabel; Michenthaler, Helene; Sulaj, Alba; Moyschewitz, Elisabeth; Krstic, Jelena; Galhuber, Markus; Xu, Ruonan; Riahi, Zina; Wang, Tongtong; Vujic, Nemanja; Amor, Melina; Zenezini Chiozzi, Riccardo; et al. (Nature Communications, 2024)
In obesity, sustained adipose tissue (AT) inflammation constitutes a cellular memory that limits the effectiveness of weight loss interventions. Yet, the impact of fasting regimens on the regulation of AT immune infiltration is still elusive. Here we show that intermittent fasting (IF) exacerbates the lipid-associated macrophage (LAM) inflammatory phenotype of visceral AT in obese mice. Importantly, this increase in LAM abundance is strongly p53 dependent and partly mediated by p53-driven adipocyte apoptosis. Adipocyte-specific deletion of p53 prevents LAM accumulation during IF, increases the catabolic state of adipocytes, and enhances systemic metabolic flexibility and insulin sensitivity. Finally, in cohorts of obese/diabetic patients, we describe a p53 polymorphism that links to efficacy of a fasting-mimicking diet and that the expression of p53 and TREM2 in AT negatively correlates with maintaining weight loss after bariatric surgery. Overall, our results demonstrate that p53 signalling in adipocytes dictates LAM accumulation in AT under IF and modulates fasting effectiveness in mice and humans.
Gesehen am 23.08.2024